Effect of mechanical stimulation on tissue heterotopic ossification: an in vivo experimental study - Zhu, Zhengya; He, Zhongyuan; Tang, Tao; Wang, Fuan; Chen, Hongkun; Zhou, Jiaxiang; Lin, Chengkai; Chen, Guoliang; Wang, Jianmin; Li, Jianfeng; Liu, Xizhe; Zhou, Zhiyu; et al. (Frontiers in Physiology, 2023)
Background: Heterotopic ossification of tendons and ligaments (HOTL) is a common clinical condition characterized by the absence of discernible features and a lack of effective treatment. In vitro experiments have demonstrated that mechanical stimulation can induce cell differentiation toward osteogenesis, thereby promoting heterotopic ossification. Currently, there are few experimental designs aimed at inducing ligament stretching in mice, and the mechanism of heterotopic ossification may not entirely mirror that observed in clinical cases. Therefore, there is an urgent imperative to develop a novel and feasible animal model. Methods: In this study, all the Enpp1 gene deficiency mice (a mouse model with heterotopic ossification of multiple ligaments) were divided into three groups: the control group, the spinal brake group, and the hyperactive group (treadmill training group). An external spinal fixation device was designed to restrict mice’s spinal flexion and extension at 6 weeks of age. The brace was adjusted weekly according to the changes in the size of the mice. Additionally, treadmill training was used to increase activity in the spinal ligaments and Achilles tendons of the mice. Micro-CT scanning and HE staining were performed at 12, 20, and 28 W to evaluate the degree of ossification in the spinal ligament and Achilles tendon. What’s more, As one of the mechanical stimulation transduction signals, YAP plays a crucial role in promoting osteogenic differentiation of cells. Immunofluorescence was utilized to assess YAP expression levels for the purpose of determining the extent of mechanical stimulation in tissues. Results: Our findings showed that a few ossification lesions were detected behind the vertebral space of mice at 8 weeks of age. Spinal immobilization effectively restricts the flexion and extension of cervical and thoracic vertebrae in mice, delaying spinal ligament ossification and reducing chronic secondary spinal cord injury. Running exercises not only enhance the ossification area of the posterior longitudinal ligament (PLL) and Achilles tendons but also exacerbate secondary spinal cord injury. Further immunofluorescence results revealed a notable increase in YAP expression levels in tissues with severe ossification, suggesting that these tissues may be subjected to higher mechanical stimulation. Conclusion: Mechanical stimulation plays a pivotal role in the process of heterotopic ossification in tissues. Our study provided valid animal models to further explore the pathological mechanism of mechanical stimulation in HOTL development.